Reversible or not? Distinguishing agglomeration and aggregation at the nanoscale - Sokolov, S; Tschulik, K; Batchelor-McAuley, C; Jurkschat, K; Compton, R (ACS Publications, 2015)
Nanoparticles are prone to clustering either via aggregation (irreversible) or agglomeration (reversible) processes. It is exceedingly difficult to distinguish the two via conventional techniques such as dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), or electron microscopy imaging (scanning electron microscopy (SEM), transmission electron microscopy (TEM)) as such techniques only generally confirm the presence of large particle clusters. Herein we develop a joint approach to tackle the issue of distinguishing between nanoparticle aggregation vs agglomeration by characterizing a colloidal system of Ag NPs using DLS, NTA, SEM imaging and the electrochemical nanoimpacts technique. In contrast to the conventional techniques which all reveal the presence of large clusters of particles, electrochemical nanoimpacts provide information regarding individual nanoparticles in the solution phase and reveal the presence of small nanoparticles (<30 nm) even in high ionic strength (above 0.5 M KCl) and allow a more complete analysis. The detection of small nanoparticles in high ionic strength media evidence the clustering to be a reversible process. As a result it is concluded that agglomeration rather than irreversible aggregation takes place. This observation is of general importance for all colloids as it provides a feasible analysis technique for a wide range of systems with an ability to distinguish subtly different processes.